One new berberine from the branches and leaves of Polyalthia obliqua Hook.f. & Thomson. Issue 20 (17th October 2016) - Wu, Li-Jun; Zheng, Cai-Juan; Wang, Liu-Kai; Han, Chang-Ri; Song, Xiao-Ping; Chen, Guang-Ying; Zhou, Xue-ming; Wu, Shou-yuan; Li, Xiao-bao; Bai, Meng; Liu, Chun-xin; Yao, Jun
Abstract: One new alkaloid consanguine B (1 ), together with 10 known alkaloids (2 –11 ), were isolated from ethanol extract of the branches and leaves of Polyalthia obliqua Hook.f. & Thomson collected in the Hainan Province, China. Their structures were elucidated by the detailed analysis of comprehensive spectroscopic data. All compounds were evaluated for their cytotoxic activities. Compound1 showed weak cytotoxic activities against Hela and MCF-7 human cancer cell lines. Abstract :